Enhancement of solubility, dissolution release profile and reduction in ulcerogenicity of piroxicam by inclusion complex with skimmed milk. (November 2014) - Sanka, Krishna; Munjulury, Venkata Saidheeraj; Mohd, Abdul Bari; Diwan, Prakash V.
Abstract Context: Piroxicam (PXM), a non-steroidal anti-inflammatory drug which is poorly soluble in water and ulcerogenic. Milk has been used against the gastric disturbances caused by non-steroidal anti-inflammatory drugs. In this study, skimmed milk (SKM) is used as the carrier for inclusion complex (IC) due to its surface active agent and amino acid content. Purpose: To enhance the solubility, dissolution rate and prevent ulcerogenicity of PXM though IC with SKM. Methods: IC of PXM were prepared with SKM by solvent evaporation method using rota evaporator and were evaluated for solubility, dissolution, solid state characterization, drug excipient interaction, rat intestinal permeation, ulcerogenicity and histopathological studies. Results: Solubility of PXM was enhanced 2.5 times with IC. The dissolution release and amount of PXM permeated through rat small intestine was enhanced significantly with IC. Decreases in the gastric lesion index values of IC were observed than physical mixture (PM) and free PXM. The histopathological studies revealed significant reduction in ulceration in rat stomach after treatment with IC. Conclusion: It is concluded that SKM is a good carrier to prepare IC of PXM for oral administration.